Digital Supply Chain Trends in the World Economy - V.V. Yankovskaya; Iu.V. Panko; Z.I. Kruglyak; A.V. Kolesnikov; V.E. Kosarev (International Journal of Supply Chain Management, 2020)
Abstract— In connection with the ongoing changes in the world economy, associated with the acceleration of scientific and technological progress, changing as a result of the introduction of new technologies, the structure of production, the expansion of the use of digital technologies - there are positive structural changes in many industries. Views and approaches to solving various tasks and problems of innovative development are also changing. The paper presents the results of analyzing the trend of the digitalization process. It is concluded that public policy is the main factor and tool for the development of the digital supply chain of economy, and a forecast is made for the number of participants using various types of communication. The development of an innovative economy and the introduction of digital technologies clearly lead to the transformation and revision of the foundations of the global economy, as the modern economy is the economy of database management. In this paper, as far as statistical information is available, the main trends in the development of digital technologies in supply chain process are considered. The paper focuses on the availability of the Internet for households, the quality and speed of communication, the reasons that affect it, and the presence of cause-and-effect relationships. Analytical data on the share of the digital supply chain in GDP, government support for digital technologies, and investment in this area of the economy are provided for some developed and developing countries. The most frequently used digital technologies in supply chain that have prospects for both developed and developing countries are highlighted. The study provides data on the possibility of using digital technologies in the banking sector in order to reduce cash transactions.